Pengaruh Pemberian Buah Pisang Mas Terhadap Peningkatan Kadar Hb Pada Ibu Hamil Trimester III - Elsa Kumala Safitri; Miftahul Mualimah; Herliana Riska (SEAJOM: The Southeast Asia Journal of Midwifery, 2019)
Hemoglobin is a protein-rich substance bezi, Have affinity (power team) against oxygen and with oxygen it forms a oxihemoglobin in red blood cells. The goal in this research is to know the influence of banana fruit mas to increased hemoglobin on pregnant women trimester III in BPM Ny "B" Ngasem Regency Kediri Year 2017. In this research method using alphabets experiment and approach Pre alphabets experiment with Purposive Sampling. This research was conducted in BPM Ny "B" Ngasem Regency Kediri Year 2017. Instruments in use are sheets of observation, data analysis with the iji Wlcoxon Signed Rank. Results of research of banana fruit mas on pregnant women this trimester III that the magnitude of the value of ρ is less than the value of 0.000 α = 0.05 (0.000 < 0.05) so that H0 is rejected and the H1 is accepted means there is influence of hemoglobin levels before and after the given bananas mas against peningktan the levels of haemoglobin in pregnant women Trimester III in BPM Ny. " B “ Ngasem Regency Kediri year 2017. With this expected to consume fruit banana mas on pregnant women may help lower III trimester anemia with practical.